1997
DOI: 10.1515/cclm.1997.35.6.415
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione and Nitric Oxide Concentrations in Glutamine-Infused Rabbits with Intestinal Ischaemia/Reperfusion

Abstract: Intestinal ischaemia/reperfusion causes formation of reactive oxygen intermediates which lead to mucosal cell injury. Glutathione, a scavenger of reactive oxygen intermediates, protects tissues from reactive oxygen intermediate-mediated cell injury. Nitric oxide is a lipophilic gas and its synthesis is stimulated by ischaemic conditions. In this experimental study, we aimed to investigate the role of i. v. L-glutamine infusion on mucosal tissue glutathione and serum nitric oxide concentrations in intestinal is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
2
8
0
Order By: Relevance
“…This could point to a reduction in the rate of muscle glutamine de novo synthesis. However, if, similar to other studies, glutamine efflux from muscle would have been increased 48 hours after surgery, then the unchanged plasma glutamine Ra observed in this most recent study could only be explained by the fact that the increased release from muscle is offset by a decreased release from sources other than muscle such as liver. We previously showed that in pigs the liver switches from glutamine production in the preoperative setting to glutamine consumption after operation.24 Changes in the flow of glutamine between organs apparently may occur without the whole-body plasma glutamine Ra being altered.…”
Section: Kinetics Of Glutaminesupporting
confidence: 82%
“…This could point to a reduction in the rate of muscle glutamine de novo synthesis. However, if, similar to other studies, glutamine efflux from muscle would have been increased 48 hours after surgery, then the unchanged plasma glutamine Ra observed in this most recent study could only be explained by the fact that the increased release from muscle is offset by a decreased release from sources other than muscle such as liver. We previously showed that in pigs the liver switches from glutamine production in the preoperative setting to glutamine consumption after operation.24 Changes in the flow of glutamine between organs apparently may occur without the whole-body plasma glutamine Ra being altered.…”
Section: Kinetics Of Glutaminesupporting
confidence: 82%
“…Indeed, Cit-Arg cycling was upregulated in endotoxemic rats (16), supporting regulation of NO production by Gln. On the other hand, it has also been suggested that Gln supplementation inhibits NO production (1,14). In our study, Gln net consumption in the gut appeared to have a stimulating effect on NO production.…”
Section: Discussionsupporting
confidence: 56%
“…Ischaemia–reperfusion (I/R) injury is the underlying cause of morbidity and mortality in several diseases, including stroke, myocardial infarction and acute renal tubular necrosis 1 . Ischaemia causes a depletion of ATP and an accumulation of toxic metabolites, whereas the subsequent reperfusion injury stimulates the production of reactive oxygen intermediates 2 . The pathogenic mechanisms that underlie coronary atherosclerotic heart disease are undefined at present 3…”
Section: Introductionmentioning
confidence: 99%